Effects of prophylactic ankle supports on vertical ground reaction force during landing: A meta-analysis - Niu, W.; Feng, T.; Wang, L.; Jiang, C.; Zhang, M. (Journal of Sports Science & Medicine, 2016)
There has been much debate on how prophylactic ankle supports (PASs) may influence the vertical ground reaction force (vGRF) during landing. Therefore, the primary aims of this meta-analysis were to systematically review and synthesize the effect of PASs on vGRF, and to understand how PASs affect vGRF peaks (F1, F2) and the time from initial contact to peak loading (T1, T2) during landing. Several key databases, including Scopus, Cochrane, Embase, PubMed, ProQuest, Medline, Ovid, Web of Science, and the Physical Activity Index, were used for identifying relevant studies published in English since inception to April 1, 2015. The computerized literature search and cross-referencing the citation list of the articles yielded 3,993 articles. Criteria for inclusion required that 1) the study was conducted on healthy adults; 2) the subject number and trial number were known; 3) the subjects performed landing with and without PAS; 4) the landing movement was in the sagittal plane; 5) the comparable vGRF parameters were reported; and 6) the F1 and F2 must be normalized to the subject`s body weight. After the removal of duplicates and irrelevant articles, 6, 6, 15 and 11 studies were respectively pooled for outcomes of F1, T1, F2 and T2. This study found a significantly increased F2 (.03 BW, 95% CI: .001, .05) and decreased T1 (-1.24 ms, 95% CI: -1.77, -.71) and T2 (-3.74 ms, 95% CI: -4.83, -2.65) with the use of a PAS. F1 was not significantly influenced by the PAS. Heterogeneity was present in some results, but there was no evidence of publication bias for any outcome. These changes represented deterioration in the buffering characteristics of the joint. An ideal PAS design should limit the excessive joint motion of ankle inversion, while allowing a normal range of motion, especially in the sagittal plane.